Pragmatic Instruction Effects on Studentsâ EFL Production: A Qualitative Analysis - Purwanti, Indah Tri (Proceedings of the UR International Conference on Educational Sciences, 2018)
The present study aims to investigate whether the implementation of pragmatic instruction would change the studentsâ pragmatic production of English requests. The pragmatic instruction was based on an approach proposed by MartÃnez Flor and UsÃ³ Juan (2006). Thirty-four undergraduate students participated in the study. A discourse completion task was used to collect the data that were administered before and after the treatment. During the treatment, the participants followed the six phases of the approach. After the treatment, studentsâ pre-test was compared to that of the post-test. A qualitative analysis was used to scrutinise the request strategies. The result revealed that studentsâ production of requests was improved. Internal modifications, lexical and phrasal modifications, were sometimes used. The participants often employed the external modification, grounders. Besides, the result also displayed first language transfer.